Transference, tradition, technology : Native new media : exploring visual & digital culture. - Beaucage, Marjorie; Claxton, Dana; Dempsey, Shawna; Gagnon, Monika; Hopkins, Candice; Kunuk, Puhipau & Zacharias; Loft, Steven; Masayesva, Victor; Maskegon-Iskwew, Ahasiw; Todd, Loretta; Townsend, Melanie; Young-Ing, Greg (Banff : Walter Phillips Gallery, 2005)
Adams, kc ; Cayuga, Cat ; Claxton, Dana ; Cuthand, Thirza ; Foster, Stephen ; Fragnito, Skawennati Tricia ; Garneau, David ; Kunuk, Zacharias ; Loft, Steven ; Longboy, Zachery ; MacDonald, Mike ; Maskegon-Iskwew, Ahasiw ; Naponse, Darlene ; Niro, Shelley ; Obomsawin, Alanis ; Sainte-Marie, Buffy ; Yuxweluptun, Lawrence Paul
Biog. auteurs p. 219-223
Engels
boek
Keywords: Canada